Dialect in the Viking-Age Scandinavian diaspora: the evidence of medieval minor names - Rye, Eleanor (2016)
This thesis investigates the Scandinavian contribution to medieval microtoponymic vocabulary in two areas of northwest England, Wirral, part of the historic county of Cheshire in the north-west Midlands, and an area of the county of Cumbria, the West Ward of Westmorland Barony. It is shown that there was far greater Scandinavian linguistic influence on the medieval microtoponymy of the West Ward than on the medieval microtoponymy of Wirral. This thesis also assesses what conclusions can be drawn from the use of Scandinavian derived place name elements in microtoponyms. Scandinavian influence on microtoponymy has previously been interpreted, at one extreme, as evidence for Scandinavian settlement, and, at the other extreme, only as reflecting widespread Scandinavian influence on the English language and English naming practices. The relationship between Scandinavian settlement and Scandinavian influence on naming micropotonymy is explored by considering the microtoponymic evidence in the light of evidence illuminating the circumstances of Scandinavian settlement in the case-study areas, and by considering the evidence from the case-study areas within the wider context of Scandinavian influence on English naming practices. The substantial Scandinavian substantial influence on major place names in both areas confirms that Scandinavian had been spoken in Wirral and the West Ward. However, the Scandinavian contribution to toponymic vocabulary as recorded in the late medieval period was very different in the two areas, hinting at the indirectness of the link between Scandinavian settlement and influence on later microtoponymy. Indeed, detailed consideration of the use of individual Scandinavian-derived place name elements at a national level indicates that the areas over which some Scandinavian-derived place-name elements were used increased during the Middle English period. The factors underlying the usage of Scandinavian derived toponymic vocabulary in the late-medieval period are therefore more varied than has sometimes been acknowledged.